New Measurable Indicator for Tuberculosis Case Detection - Borgdorff, Martien W. (Centers for Disease Control and Prevention, 2004)
The World Health Organization's goal for tuberculosis (TB) control is to detect 70% of new, smear-positive TB cases and cure 85% of these cases. The case detection rate is the number of reported cases per 100,000 persons per year divided by the estimated incidence rate per 100,000 per year. TB incidence is uncertain and not measured but estimated; therefore, the case detection rate is uncertain. This article proposes a new indicator to assess case detection: the patient diagnostic rate. The patient diagnostic rate is the rate at which prevalent cases are detected by control programs and can be measured as the number of reported cases per 100,000 persons per year divided by the prevalence per 100,000. Prevalence can be measured directly through national prevalence surveys. Conducting prevalence surveys at 5- to 10-year intervals would allow countries with high rates of disease to determine their case detection performance by using the patient diagnostic rate and determine the effect of control measures.